NILAI PENDIDIKAN MORAL DALAM NOVEL MADOGIWA NO TOTTO-CHAN KARYA TETSUKO KUROYANAGI - Andari, Novi (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2011)
Abstrak. A literary work obtains its inspiration from a social phenomenon. It is also possible, however, that a literary work inspires a society to create a social phenomenon. This article discusses the moral values in a novel entitled Totto-chan Gadis Cilik di Jendela (Madogiwa No Totto-Chan). It tells about a social phenomenon in Japan portrayed through an elementary school little girl of a first grade who was unable to focus on her learning process. Â Kata kunci: social phenomenon, basic concept of education, moral values